Driving me crazy : fun-onwheels jokes - Keller, Charles (New York : Pippin Press, 1989)
Jokes and riddles about cars, buses, trucks, bicyclesm motorcycles, and other vehicles on wheels.
Keywords: Motor vehicles -- Juvenile humor; Wheels -- Juvenile humor; Riddles, Juvenile; Wit and humor